PENGARUH PENGALAMAN KERJA, MOTIVASI INTRINSIK DAN KEPUASAN KERJA KARYAWAN TERHADAP KINERJA KARYAWAN DEPO PELITA PT PELITA SATRIA PERKASA SOKARAJA - Chalimatus Sa'diyah; Hermin Endratno (JBIMA (Jurnal Bisnis dan Manajemen), 2013)
This study aims to determine the effect of work experience, intrinsic motivation and job satisfaction on performance, either partially or simultaneously. The methods used in sampling is purposive sampling, the sampling is based on the consideration to fit the study criteria in order to improve the accuracy of the sample. With the criteria of permanent employees who work a minimum of 1 year. The analytical method used was multiple linear regression test with a significant level (α) 0.05.The results of this study concluded that the partial work experience influence the performance of employees, with a significant value of 0.000 is less than 0.05. Partially intrinsic motivation does not affect the performance of employees, with a significant value of 0.098 is more than 0.05. Job satisfaction is partially not affect the performance of employees, with a significant value of 0.059 is more than 0.05. Work experience, intrinsic motivation and job satisfaction simultaneously affect the performance of employees, with a significant value of 0.000 is less than 0.05.Suggestions for Leadership Depo Pelita should further enhance the intrinsic motivation of employees by conducting trainings such as motivation training and rewards for employees who excel. In addition to the leadership of Depo Pelita can also further enhance job satisfaction by giving employees a raise or benefits. For employees Depo Pelita should further improve their performance by learning from other employees who have good performance so that all employees can master their main job.